Answer:
Step-by-step explanation:
X Y X Y
0 3 0 5
1 7 1 8
2 11 2 11
3 15 3 14
4 19 4 17
Answer:
15ft
Step-by-step explanation:
Draw out the picture and use the Pythagorean theorem (equation is written in blue) to solve.
View Image
99.69/100=.9969
.9969*20=19.938
Ramon would receive ~ $19.94
1. x - 4
x - 6|x² - 10x + 24
- (x² - 6x)
-4x + 24
- (4x + 24)
0
The answer is C.
2. A. 9x² + 12x - 3
3(x²) + 3(4x) - 3(1)
3(x² + 4x - 1)
B. 9x² + 3x - 5
Not Factored
C. 6x² + 10x - 4
2(3x²) + 2(5x) - 2(2)
2(3x² + 5x - 2)
2(3x² + 6x - x - 2)
2(3x(x) + 3x(2) - 1(x) - 1(2))
2(3x(x + 2) - 1(x + 2))
2(3x - 1)(x + 2)
D. 6x² + 7x - 6
Not Factored
The answer is C.
3. 3x³ - 4x² + 3x - 6
x + 2|3x⁴ + 2x³ - 5x² + 0x - 4
- (3x⁴ + 6x³)
-4x³ - 5x²
- (-4x³ - 8x²)
3x² + 0x
- (3x² + 6x)
-6x - 4
- (-6x - 12)
8
The answer is A.
Answer:
x + 1
y = 9
Step-by-step explanation:
In order to solve this question we need to represent "y "in terms of "x" in the first equation, and the plug in the "y" value in the first equation into the second one. Luckily for us in the first equation it already shows what "y" is equal to in terms of "x" (based on the first equation y = -x + 10). Now we just need to plug in the value that we got instead of "y" in the second equation, and so we get....
y = 7x + 2
(plug in the y value and get the following ….)
-x + 10 = 7x + 2
(now just solve the following equation)
-x + 10 + x = 7x + 2 + x
10 = 8x + 2
10 - 2 = 8x + 2 - 2
8 = 8x
8/8 = 8x/8
1 = x
Now that we know the value of "x", all we need to do now is substitute the value of "x" into any of the equations and we will get the value of "y". So we do the following.....
y = 7x + 2
y = 7(1) + 2
y = 7 + 2
y = 9